An Assessment of Palaeodepositional Environment and Thermal Maturity of Upper Palaeozoic Sediments of Peninsular Malaysia by Organic Geochemical and Petrological Methods - Mohamed Ibrahim, Amer; Hasiah Abdullah, Wan (Malaysian Journal of Science, 2002)
Six organic-rich sediments of the Upper Palaeozoic Kuantan Group from East Pahang were analysed by means of organic petrological and geochemical methods. The aim of this study is to assess the type of organic matter, maturity and depositional environments based primarily on biomarker (geochemical fossils) distributions. The gas chromatograms of the saturated hydrocarbon fractions of the Charu and Sagor shales and coaly shales display a smooth high end-member distribution of n-alkanes extending beyond $nC_{30}$. A relatively lower abundance of n-alkanes is displayed by a limestone sample analysed. Most of these samples show evidence of slight biodegradation as suggested by the presence of unresolved complex compounds and the loss of some of the lower molecular weight n-alkanes. The strong predominance of high molecular weight n-allcanes in the shales / coaly shale of the Charu and Sagor formations suggest significant input of higher land plant organic matter into these sediments. The Panching limestone sample is dominated by $nC_{17}$ Ã¢â‚¬â€ $nC_{19}$ alkanes suggesting significant contributions of algal-derived organic matter. The even n-alkane predominance commonly associated with limestone is apparent within the medium range ($nC_{14}$ Ã¢â‚¬â€ $nC_19$) of the Panching limestone analysed. The possible presence of a $C_{21}$ highly branched isoprenoid is noted in this limestone sample but is not observed in the other samples. The lack of higher land plant-derived organic matter within the Panching limestone sample is evident from the low concentration of higher molecular weight n-alkanes compared to the Charu and Sagor sediments. The presence of significant marine influence in all of the samples studied is suggested by the high abundance of tricyclic terpanes. The 22S/22S+22R $C_{32}$ hopane has reached equilibrium, and this is supported by the high maturity level as indicated by the vitrinite reflectance data (1.08 Ã¢â‚¬â€ 1. l3%Ro). Although of high maturity, the samples are still within the oil window maturity range, suggesting these samples have not been too severely effected by thermal metamorphism or the active tectonic activities of the Eastern belt of Peninsular Malaysia.